Antimicrobial and Cytotoxic Activity of Fruit Extract from Syzygium cumini (L.) Skeels - Migliato, Ketylin F. [UNESP]; Mello, Joao C. P.; Higa, Olga Z.; Rodas, Andrea C. D.; Correa, Marcos Antonio [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Pizzolitto, Antonio Carlos [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Colegio Farmaceuticos Provincia de Buenos Aires, 2010)
The aim of the present study was to evaluate the antimicrobial and cytotoxic activity of the ethanolic extract of S. cumini according to the Clinical and Laboratory Standards Institute reference method (with modifications), determining the minimal inhibitory and lethal concentration. Activity against Gram-positive (Staphylococcus aureus and S. epidermidis), Gram-negative (Pseudomonas aeruginosa) and yeast of Candida sp and Cryptococcus neoformans was evaluated. The effects of the fruit extract were examined in hamster cells ovaries in concentrations ranging from 1250.0 a 4.9 mu g/ml, measuring the reduction of the tetrazolium salt 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulphophenyl)-2H-tetrazolium. The extract showed both bactericidal and fungicidal activity among the various microorganisms tested and the MIC ranging from 7.8 to 250 mu g/ml. The MIC, MBC and MFC should values that were similar for all the microorganisms. Cytotoxicity index of the dried extract corresponded to the concentration of 400 mu g/ml. The extract could potentially be used in topical antimicrobial products. Thus, the activity of extract was potent to bacteria and mainly to non-albicans species and C. neoformans.
Keywords: Antibacterial; Antifungal; Antimicrobial activity; Cytotoxic activity; Jambolan; Minimum inhibitory concentration; Minimal lethal concentration; Syzygium cumini